Delay in termination of pregnancy among unmarried adolescents and young women attending a tertiary hospital abortion clinic in Trivandrum, Kerala, India - Sowmini C.V (Reproductive Health Matters, 2013)
Unwed pregnancy among adolescents is a disturbing event in Indian belief-systems, and very young motherhood limits girls’ social, economic and educational prospects. Girls who seek abortions are always at higher risk for delay in care seeking; this paper looks at the reasons why. It reports the experiences of 34 unmarried adolescent girls and young women, aged 10–24 years, who obtained induced abortion from a tertiary care abortion clinic over a period of seven months in 2004. Ten were below 19 years of age, the rest were 20–24 years. Only eight of the 34 pregnancies were <12 weeks. The reasons for delay were fear of disclosure, lack of any support system and scarcity of resources. In 30 cases, the decision to terminate was made jointly with family members, especially the mother. Only half knew about contraception, of whom two used condoms. Only two of the partners accompanied the girl to the abortion clinic and another two offered some financial support. Because of the conflict between wanting to have sex and feeling guilty about it, these young people experienced terrible distress in the course of unwanted pregnancy. Comparing the adolescents who attended the clinic in 2004 with those we have seen in 2012–2013, the paper shows that as regards the essentials, much has remained the same.